Tropical myositis: ultrastructural studies. - Taylor, J F (1976)
Specimens of muscle were obtained from non-suppurating lesions of nine patients with tropical myositis. When examined in an electron microscope, these revealed patchy myocytolysis with loss of band structure. Perimysial cells were also degenerate. Sections from two out of nine patients revealed intracellular vesicles, about 80 nm in diameter, some of which contained 10 nm granules. These vesicles were seen budding from cell membranes and resembled virus particles. The focal necrosis with which they are associated and their absence from control sections support the concept that they are related to the disease process.